(3GdRgOs - (3CMeO Hf eMeO Hf MfHd, CHh YHO Gddg, GdTjHGfqj GdhGFdj,J (B241 (3g` s
(3ChdgG (B:s
(3bGd PcQ QShd Gddg Udi Gddg Ydjg hSde (B" (3QLd fGe djdI MJi CUHM bGd PGc QLd (B" s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B" (3Ggd GdeYQha ai GdOfjG ge Cgd GdeYQha ai GdBNQI hCf Cgd GdefcQ aiGdOfjG ge Cgd GdefcQ ai GdCNQI (B" s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B96s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1422s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(292 (3c(B) s
Keywords: (3Gdabg GdMfHdjs